Domestication affects the structure, development and stability of biobehavioural profiles. Issue 1 (December 2015) - Kaiser, Sylvia; Hennessy, Michael; Sachser, Norbert
Abstract Domestication is an evolutionary process during which the biobehavioural profile (comprising e.g. social and emotional behaviour, cognitive abilities, as well as hormonal stress responses) is substantially reshaped. Using a comparative approach, and focusing mainly on the domestic and wild guinea pig, an established model system for the study of domestication, we review (a) how wild and domestic animals of the same species differ in behaviour, emotion, cognition, and hormonal stress responses, (b) during which phases of life differences in biobehavioural profiles emerge and (c) whether or not animal personalities exist in both the wild and domestic form. Concerning (a), typical changes with domestication include increased courtship, sociopositive and maternal behaviours as well as decreased aggression and attentive behaviour. In addition, domestic animals display more anxiety-like and less risk-taking and exploratory behaviour than the wild form and they show distinctly lower endocrine stress responsiveness. There are no indications, however, that domestic animals have diminished cognitive abilities relative to the wild form. The different biobehavioural profiles of the wild and domestic animals can be regarded as adaptations to the different environmental conditions under which they live, i.e., the natural habitat and artificial man-made housing conditions, respectively. Concerning (b), the comparison of infantile, adolescent and adult wild and domestic guinea pigs shows that the typical biobehavioural profile of the domestic form is already present during early phases of life, that is, during early adolescence and weaning. Thus, differences between the domestic and the wild form can be attributed to genetic alterations resulting from artificial selection, and likely to environmental influences during the pre- and perinatal phase. Interestingly, the frequency of play behaviour does not differ between the domestic and wild form early in life, but is significantly higher in domesticated guinea pigs at later ages. Concerning (c), there is some evidence that personalities occur in both wild and domestic animals. However, there may be differences in which behavioural domains – social and sexual behaviour, emotionality, stress-responsiveness – are consistent over time. These differences are probably due to changing selection pressures during domestication.